The dimer state of GyrB is an active form: implications for the initial complex assembly and processive strand passage - Wu, Jinjun (Oxford University Press, 2011)
In a previous study, we presented the dimer structure of DNA gyrase B′ domain (GyrB C-terminal domain) from Mycobacterium tuberculosis and proposed a ‘sluice-like’ model for T-segment transport. However, the role of the dimer structure is still not well understood. Cross-linking and analytical ultracentrifugation experiments showed that the dimer structure exists both in the B′ protein and in the full-length GyrB in solution. The cross-linked dimer of GyrB bound GyrA very weakly, but bound dsDNA with a much higher affinity than that of the monomer state. Using cross-linking and far-western analyses, the dimer state of GyrB was found to be involved in the ternary GyrA–GyrB–DNA complex. The results of mutational studies reveal that the dimer structure represents a state before DNA cleavage. Additionally, these results suggest that the dimer might also be present between the cleavage and reunion steps during processive transport.